2006
DOI: 10.2527/2006.843526x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quantitative trait loci on chromosomes 1, 2, 4, and 7 on growth, carcass, and meat quality traits in backcross Meishan × Large White pigs1

Abstract: The aim of this work was to estimate whether genetic dissection of QTL on chromosomes 1, 2, 4, and 7, detected in an F2 Meishan x Large White population, can be achieved with a recombinant back-cross progeny test approach. For this purpose, a first generation of backcross (BC1) was produced by using frozen semen of F1 Large White x Meishan boars with Large White females. Four BC1 boars were selected because of their heterozygosity for at least 1 of the 4 regions. The BC1 boars were crossed with Large White sow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
38
2
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 19 publications
2
38
2
5
Order By: Relevance
“…The additive effect of the QTL was 0.21 cm, with the Large White allele increasing the LEW. Although several studies reported that there were significant QTL affecting LP and LEA around this region using different experimental animals (Sato et al, 2003;Yue et al, 2003;Sanchez et al, 2006;Uemoto et al, 2008), no QTL for LP and LEA with significant level were detected in the present study. This phenomenon might be due to the differences of experimental designs as well as statistical models.…”
Section: Sw2155contrasting
confidence: 45%
“…The additive effect of the QTL was 0.21 cm, with the Large White allele increasing the LEW. Although several studies reported that there were significant QTL affecting LP and LEA around this region using different experimental animals (Sato et al, 2003;Yue et al, 2003;Sanchez et al, 2006;Uemoto et al, 2008), no QTL for LP and LEA with significant level were detected in the present study. This phenomenon might be due to the differences of experimental designs as well as statistical models.…”
Section: Sw2155contrasting
confidence: 45%
“…Assim como no presente trabalho, Sanchez et al (2006) encontraram QTL para GPD na posição distal do SSC1 (87cM) ao estudarem uma população Meishan x Large White. Beeckmann et al (2003) encontraram QTL para CR a 117,2cM e 74,3cM e para GPD a 59,7cM, no SSC1 de suínos selvagens europeus x Pietrain.…”
Section: Resultsunclassified
“…At the QTL for age at puberty on SSC7, one interesting phenomenon is that the favourable QTL allele originates from the Duroc breed, which is in contradiction with the breed characteristic differences for this trait. This observation has been repeatedly documented in many QTL studies around this region, such as the QTL for fat androstenone levels [21] and for QTL for age at puberty in gilts average daily gain [26]. The reason for this remains unknown.…”
mentioning
confidence: 97%
“…The two QTL regions on SSC7 and SSC1 are of particular interest, showing highly significant associations across different resource populations. Future work will be directed at fine mapping of the QTL identified using additional markers and advanced intercross populations or recombination backcross populations [26].…”
mentioning
confidence: 99%